Proposed Negative Statutory Instruments under the European Union (Withdrawal) Act 2018 : Draft Veterinary Surgeons and Animal Welfare (Amendment) (EU Exit) Regulations 2019 : 13th Report of Session 2017-19 /: Draft Veterinary Surgeons and Animal Welfare (Amendment) (EU Exit) Regulations 2019 : 13th Report of Session 2017-19. ([2019-01-24]) - Unknown
No abstract available